The theories of justice, of John Rawls and Norman Daniels, applied to health - Paranhos, Denise Gonçalves de Araújo Mello (2022)
This article focus on the theories formulated by John Rawls and Norman Daniels. Rawls proposes that the distribution of resources must occur in two stages. At first, the concern would be with the equal distribution of basic rights and responsibilities. Secondly, according to the principle of difference, unjust inequalities would be compensated for, particularly those that reach the most disadvantaged, ensuring everyone equal opportunities. His focus was the distribution of primary social goods, which don’t include health, considered by him as a natural primary good. Daniels adapted the Rawlsian theory, extending it to encompass health (not just health care). Daniels’s theory, while placing health in its broad sense and with special moral status to be protected by the principles of freedom, difference and equality of opportunities, strengthens the theory of Justice of Rawls. Although they do not present a definitive solution on how to distribute resources fairly, the theories of Rawls and Daniels lead to reflections about the need to reduce unfair inequalities in health, as well as give rise to debates on issues such as social cooperation, freedoms, equality, allocation of scarce resources, adequate distribution of income and wealth, and opportunities.